The Human Capital Retention Strategies that Local Authorities in Zimbabwe Can Adopt for Successful Talent Retention - Mabika, Henry (International Journal of Management and Sustainability, 2016)
There is an outcry in local authorities regarding human capital flight and poor service delivery. The ability of local authorities to retain qualified personnel is reportedly low. To recruit and retain experienced, educated and dedicated personnel requires that local authorities' practice retention strategies. By retaining talent local authorities may improve their productivity as well as achieve acceptable levels of service delivery. Some of the retention strategies recommended in this paper include, induction, and training, effective communication, a good human resource function, acknowledgement of achievement and concessionary loans. The paper exposes an extensive literature search. Literature on turnover and retention was studied at length and then appropriate retention strategies to retain talent were formulated.